Aanalyses of The Financial Literacy of the Population of Mari El ("Journal "U". Economy. Management. Finance.", 2020)
Purpose of the work: to analyze the state of education of the RME population in the field of finance using a social survey. The relevance of the work lies in increasing the level of financial erudition of individuals and their families in order to increase the stability of the financial system and the economic security of the Russian Federation.
Keywords: financial literacy; money; banks